A genetic switch : phage [lambda] and higher organisms - Ptashne, Mark. (Blackwell Scientific pub. & Cell press, 1992)
The master elements of control; Protein-DNA interactions and gene control; Control circuits - setting the switch; How do we know - the key experiments; Eukaryotic gene regulation - an overview; Eukaryotic gene regulation - experiments and examples.